'Here' and 'There' in Croatian : A Case Study of an Urban Standard Variety - Žic Fuchs, Milena (1997)
This paper deals with lexical and conceptual changes in paradigms for spatial deixis in Croatian. The results show that the changes apparent in Croatian are due to urban-rural conceptual changes.
Projekt MZOS
ENG